До питання про вибір методу знеболювання для операцій на щитоподібній залозі - Попандопуло, Г. Д.; Попандопуло, А. Г.; Штода, Д. Є.; Ярощак, С. В.; Корчагін, Є. П.; Попандопуло, Д. А. (Clinical Endocrinology and Endocrine Surgery, 2009)
In article is given analysis the most acceptable method of anesthetization at operations on thyroid gland. The majority of operations was executed by authors under local infiltration anesthesia. Main advantages of this type of anesthesia are shown.